Univerzitetno izobraževanje ali novinarska praksa? Stališča urednikov slovenskih množičnih medijev - Poler Kovačič, Melita (Teorija in praksa, 2013)
The article presents the views of eleven editors from influential Slovenian news media about journalism education. An analysis of in-depth interviews revealed that the majority of the editors advocate the university education of a journalist in combination with a lot of practical training. Above all, they emphasise the importance of communication competence, while some also refer to subject-matter competence and a journalist's personal characteristics. They mostly have good experiences with students of the Journalism programme at the Faculty of Social Sciences. They see good the communication and professional competencies, knowledge of journalism roles, ethics and journalism in new media as an advantage of these students, and non-specialised knowledge as their deficiency. They are generally satisfied with the faculty programme. They suggest improvements which have for the most part already been included in the current curriculum.
Keywords: Editors; Education; Fakulteta za družbene vede; Izobraževanje; Journalism; Mass media; Množični mediji; Novinarstvo; Slovenia; Slovenija; Uredniki